A multiscale classification of urban morphology - Schirmer, Patrick Michael; Axhausen, Kay W. (Journal of Transport and Land Use, 2015)
Various studies in the field of urban planning and design have given recommendations for "good urban forms," suggesting that specific spatial characteristics inform the quality of an urban landscape and the way people perceive and behave in them. When modeling spatial behavior in the form of location choice models or hedonic prices, we should reflect these spatial characteristics through the integration of quantitative attributes such as model variables, which is currently only done in a very limited way. The increasing availability of disaggregated geodata enlarges the options to characterize urban morphology in the form of such attributes. The question for the researcher is which attributes are most useful to reflect characteristics of urban morphology and how can they be processed from the given data. In this paper, we want to address this issue and give an overview of quantitative descriptions of urban morphology. We base our work on a data model that is simple enough to allow for reproducibility in any study area. These attributes are classified in multiple scales to reflect different perceptions of urban morphology. In a case study on the canton of Zurich, we furthermore prove how these characteristics allow for the definition of urban typologies at different scales.